Differential response of idiopathic sporadic tumoral calcinosis to bisphosphonates - Balachandran, Karthik (Medknow Publications & Media Pvt Ltd, 2014)
CONTEXT: Tumoral calcinosis is a disorder of phosphate metabolism characterized by ectopic calcification around major joints. Surgery is the current treatment of choice, but a suboptimal choice in recurrent and multicentric lesions. AIMS: To evaluate the efficacy of bisphosphonates for the management of tumoral calcinosis on optimized medical treatment. SETTINGS AND DESIGN: The study was done in the endocrine department of a tertiary care hospital in South India. We prospectively studied two patients with recurrent tumoral calcinosis who had failed therapy with phosphate lowering measures. MATERIALS AND METHODS: After informed consent, we treated both patients with standard age adjusted doses of bisphosphonates for 18 months. The response was assessed by X ray and whole body 99mTc-methylene diphosphonate bone scan at the beginning of therapy and at the end of 1 year. We also estimated serum phosphate levels and urinary phosphate to document serial changes. RESULTS: Two patients (aged 19 and 5 years) with recurrent idiopathic hyperphosphatemic tumoral calcinosis, following surgery were studied. Both patients had failed therapy with conventional medical management − low phosphate diet and phosphate binders. They had restriction of joint mobility. Both were given standard doses of oral alendronate and parenteral pamidronate respectively for more than a year, along with phosphate lowering measures. At the end of 1 year, one of the patients had more than 95% and 90% reduction in the size of the lesions in right and left shoulder joints respectively with total improvement in range of motion. In contrast, the other patient (5-year-old) had shown no improvement, despite continuing to maintain normophosphatemia following treatment. CONCLUSIONS: Bisphosphonate therapy in tumoral calcinosis is associated with lesion resolution and may be used as a viable alternative to surgery, especially in cases with multicentric recurrence or treatment failure to other drugs.